Smart Consumer Purchasing Decisions: The Moderating Role of Lifestyle - Yonas Ferdinand Riwu; Sari Angriany Natonis; Junita Cestilia Nenabu (International Journal of Asian Business and Management, 2024)
This research aims to analyze the influence of price on the purchase decision of Samsung smartphones with lifestyle as a moderating variable in Faculty of Economics and Business Undana Kupang students. This study uses a quantitative approach with a sample of 95 people. Data were collected using questionnaires and analyzed using simple linear regression and MRA tests with the help of IBM 29 SPSS. The results of this study show that price has a positive effect on purchase decisions, meaning that higher prices are considered indicators of product value or superiority, thus encouraging consumers to make purchases., in addition, lifestyle weakens the relationship between price and purchase decisions, meaning that the influence of price on purchase decisions becomes less significant because of consumer lifestyles. In this context, even if the price of a product or service is higher or lower, consumers' purchasing decisions are influenced more by their lifestyle than by the price itself. Smart consumers tend to price as their lifestyle improves. Smart customer signals a significant shift in the way people think about purchasing. They are beginning to realize that price does not always reflect the true value of a product. In many cases, savvy consumers are willing to pay more for higher quality, appeal, or ethical values